Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Security PT. Partamina Geothermal Energy Ulubelu - Budiman, Ali; Ardansyah, Ardansyah (Journal of Economics, Bussiness and Management Issues, 2024)
This study delves into the critical relationship between work discipline, motivation, and security performance within PT. Partamina Geothermal Energy Ulubelu. Through a survey conducted among 48 security guards, the impact of these factors was meticulously examined. Leveraging SPSS version 40 for data analysis, the research employed multiple linear regression analysis and the Pearson product moment validity test to evaluate the hypotheses. The results underscored the significant influence of both work motivation and discipline on security performance. Specifically, the findings revealed that heightened levels of motivation and adherence to work discipline correlate positively with enhanced security outcomes. Consequently, the research concludes that PT. Partamina Geothermal Energy Ulubelu's security performance is notably shaped by the interplay of these factors. This elucidation contributes to a deeper comprehension of the dynamics underpinning organizational security and underscores the pivotal role played by motivational factors and disciplined work practices within this context.